Effects of Isolated Soy Protein Supplementation Combined with Aerobic Exercise Training on Improving Body Composition, Anthropometric Characteristics and Cardiopulmonary Endurance in Women: A Pilot Study - Fang Li (MDPI AG, 2021)
Today, women are concerned with health promotion but also with improvements in body weight and shape. The purpose of this study was to investigate the effects of aerobic exercise training (AET) combined with isolated soy protein (ISP) supplementation on the body composition, anthropometric characteristics, and cardiopulmonary endurance of women. The qualified subjects were randomly assigned to AET or AET + ISP groups. Women in the AET + ISP group were given an ISP-rich supplement (40 g/day) 5 days a week for 8 weeks; those in the AET group were given the same amount of water in an identical manner. All women received 60 min of AET twice a week for 8 weeks at an intensity of 40–65% heart rate reserve (HRR) and their body composition, anthropometric characteristics, and physical fitness were measured one week before and after the 8-week AET class. A total of 16 subjects (age: 36.13 ± 5.76 years) completed the study and were included in the dataset. The results of this study show that the AET + ISP group obtained greater reductions in body weight (effect size = 0.99), body mass index (BMI, effect size = 1.04), percentage body fat (PBF, effect size = 1.18), circumferences (waist and hip, all effect sizes > 0.8), and greater gains in the percentage lean body mass (PLBM, effect size = 0.89), compared with the AET group, without significant differences in 20 m multi-stage shuttle run test (20 m MST). We conclude that there is a trend for the consumption of ISP following AET to improve the body composition and anthropometric characteristics in women, compared with those who received the same AET without ISP supplementation.